Determination of Stability Constants of Mixed Ligand Complexes of Palladium(II) with Venlafaxine Drug and Sulfur Ligands - Alturiqi, Amani S. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: To study complex formation equilibria between [Pd(V)(H2O)2]2+ and sulphur containing amino acids (L) . The concentration distribution relations of the various complex species will be evaluated. Materials and Methods: [Pd(FLX)Cl2] was prepared by heating PdCl2 (0.89 g, 5 mmole) in 100 mL water and KCl (0.75 g, 10 mmole) to 100.0Â°C for 30.0 min. After the precipitate was filtered off, it was washed sequentially with water, ethanol and diethyl ether. [Pd(V)Cl2] was converted into the diaqua form treating with two equivalents of AgNO3 overnight, and removing the AgCl precipitate by filtration through a 0.1 Î¼m pore membrane filter. Results and Discussion: The acid-based equilibria of [Pd(V)(H2O)2]2+ have been characterized by fitting their potentiometric titration data to various acidâ€“base models. The pKa1 and pK a2 values for [Pd(V)(H2O)2]2+are 4.01 and 8.15, respectively, methionine was found to form a less stable complex than S-methyl cysteine, plausibly due to the fact that the six-membered chelate ring in the former complex is energetically less favoured than the five membered ring in the latter complex. Penicillamine has three binding sites, carboxylic, amino and sulfhydryl groups. It forms the complexes 110 and 111. Conclusion: Study indicates that sulphur containing amino acids easily react with Pd(II) because of the great tendency of sulphur (a soft Lewis base) to form bonds with these metals (soft Lewis acids).